2007
DOI: 10.1080/10790268.2007.11753449
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Injury Caused by Epidural B-Cell Lymphoma: Report of Two Cases

Abstract: Background/Objective: Spinal cord injury (SCI) caused by cancer is increasing in incidence as the mean age of our patient population increases. Understanding the prognosis and functional outcome requires knowledge of diseases of the spinal column. This paper presents the unusual presentation of epidural B-cell lymphoma.Methods: Case reports.Results: Two patients presented with an unusual cause of SCI, namely B-cell lymphoma. Both patients presented with sensory deficits greater than motor deficits and gait dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
0
7
0
3
Order By: Relevance
“…Our literature review investigated ‘dural’, ‘epidural’ and ‘meningeal’ lymphomas, and identified many PDL cases, including 166 well‐documented cases . Particularly, PDLs diagnosed prior to the Revised European American Lymphoma (REAL) classification (1994), and where more recent reclassification was not possible, were not included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our literature review investigated ‘dural’, ‘epidural’ and ‘meningeal’ lymphomas, and identified many PDL cases, including 166 well‐documented cases . Particularly, PDLs diagnosed prior to the Revised European American Lymphoma (REAL) classification (1994), and where more recent reclassification was not possible, were not included.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of dural lymphoma consist of secondary dural involvement in the context of systemic or other organs' primary lymphomas, and well‐documented cases of primary dural lymphoma (PDL) are less common. Primary dural lymphomas are distinct from primary lymphomas of the central nervous system (CNS) that encompasses brain, spinal cord and subarachnoid space .…”
mentioning
confidence: 99%
“…Ekstranodal lenfomanın epidural mesafeyi etkilemesi son derece nadir görülen bir olaydır, SENHL tüm lenfomaların yaklaşık % 4'ünü oluşturur. 6 NHL vakalarında spinal kanal yerleşimi %0,1-6,5 oranında görülür. En sık epidural alanda yerleşim gösterir.…”
Section: Olgu Sunumuunclassified
“…SENHL'ların sonradan epidural boşluğa yayılan paraspinal lenf nodlarından, vertebral göv-deden veya hastalığın hematojen yayılımı ile buradaki lenfoid dokuyu infiltre etmesi sonucu kaynaklandığı düşünülmektedir. 6 Son dönemdeki immunohistokimyasal ve elektron mikroskop ça-lışmaları SENHL'ların tümünün çoğunlukla B lenfositlerden kaynaklandığını göstermiştir. Diğer tipler daha nadirdir.…”
Section: Olgu Sunumuunclassified
See 1 more Smart Citation